Stock Price Analysis in Property and Real Estate Sector Companies Listed on the Indonesian Stock Exchange - Risma Wulandari; Sumilir Sumilir; Yudi Nur Supriadi (Garuda Prestasi Nusantara Consulting, 2024)
This research is quantitative in nature which aims to determine how profitability, leverage, stock trading volume, and interest rates affect stock prices. Companies in the property and real estate sector listed on the IDX in 2020-2022 were used as samples in this study. Purposive sampling was used to determine sample selection and 38 companies were used as research samples. Panel data regression analysis using the E-Views 12 program and a significance level of 5% (0.05) was used in testing the hypothesis of this study. The test findings show that (1) there is no effect of profitability on stock prices, (2) there is an effect of leverage on stock prices, (3) there is no effect of stock trading volume on stock prices, and (4) there is no effect of interest rates on stock prices. Keywords: Profitability; Leverage; Stock Trading Volume; Interest Rate; Stock Price.